Forms in early modern utopia : the ethnography of perfection - Chordas, Nina (Ashgate, 2010)
Though much has been written about early modern imperialism in America, Nina Chordas brings a fresh perspective to the topic by exploring it through the genres of utopia. Her analysis shows early modern utopia to be not a single genre, but rather a conglomeration of many sub-genres, including travel writing, ethnography, dialogue, pastoral, and the sermon, each with its own formal and historical relationship to nascent imperialism.